From LEK to LAB: The case of the blue crab Portunus segnis in the Pelagie Islands Marine Protected Area, central Mediterranean Sea. (15th March 2022) - Maggio, Teresa; Perzia, Patrizia; Falautano, Manuela; Visconti, Giulia; Castriota, Luca
Abstract: The Non-Indigenous Species (NIS) and particularly the Invasive Alien Species (IAS) affect biodiversity at ecosystem, habitat and species level. NIS management is primarily based on species monitoring in order to prevent their spread and to limit their impact. Different NIS monitoring methods have been developed involving citizens, especially to detect easily recognizable species and, in particular, through Local Ecological Knowledge (LEK) data collection. In the present study, we report the LEK data collection conducted in the Pelagie Islands Marine Protected Area (MPA) interviewing fishers and dive masters, particularly focusing on the Lessepsian blue crab Portunus segnis (Forskål, 1775) and the subsequent sampling and validation of the species occurrence. Fistularia commersonii, Siganus rivulatus and Percnon gibbesi were the most reported species by the interviewed fishers and dive masters. P. segnis was first signaled by dive mastersand subsequently sampled for morphological and molecular validation. The LEK experience showed the importance of the collaboration between researchers and citizens in the NIS/IAS surveillance/monitoring activity; some considerations on the importance of NIS/IAS early detection and on how to achieve a good NIS/IAS surveillance system for MPAs are discussed. Graphical abstract: Image 1 Highlights: LEK allowed to record for the first time Portunus segnis in the Pelagie Islands. LEK data have been validated through morphological and molecular laboratory analyses. The sea users involvement in NIS/IAS surveillance system is the way forward. MPAs are a hub for sharing information on environmental changes.